Assimilation in Childrenâ€™s Connected Speech in â€œHiHo Kidsâ€ YouTube Videos - Swari, Radha Andhra (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2020)
AbstractThis study investigated the types of assimilation that occur in childrenâ€™s connected speech in selected â€œHiHo Kidsâ€ videos. Descriptive qualitative method was applied in this study. The source of the data were six videos from â€œHiHo Kidsâ€ YouTube channel, particularly the ones from the section of â€œKids Tryâ€ that were uploaded in September to November 2019. The data collection process involves watching and transcribing the videos manually. Two research instruments, namely the official website of Oxford Learnerâ€™s Dictionary (https://oxfordlearnersdictionaries.com) and IPA transcription website (https://ipa.typeit.org/), were used for this study, in order to check the correct pronunciation of North American (NAmE) accent, as well as typing the phonetic symbols. In terms of data analysis, the researchers identified the findings based on the theories of assimilation types by Roach (1998) and Crystal (2008). The results revealed that regressive assimilation is the most prevalent type that occurs in childrenâ€™s connected speech in the selected videos, though progressive and coalescent assimilation also occur in certain cases.Keywords: assimilation, childrenâ€™s connected speech, HiHo Kids videosÂ Abstrak Studi ini menyelidiki jenis asimilasi yang terjadi pada ujaran terhubung anak-anak dalam video